Development of highly conducting n-type micro-crystalline silicon oxide thin film and its application in high efficiency amorphous silicon solar cell. (1st August 2017) - Shin, Chonghoon; Iftiquar, S.M.; Park, Jinjoo; Kim, Youngkuk; Kim, Sangho; Jung, Junhee; Yi, Junsin
Abstract: Wide band gap and highly conducting n-type nano-crystalline silicon film can have multiple roles in thin film solar cell. We prepared phosphorus doped micro-crystalline silicon oxide films (n-μc-SiO:H) of varying crystalline volume fraction ( X c ) and applied some of the selected films in device fabrication, so that it plays the roles of n-layer and back reflector in p-i-n type solar cells. It is generally understood that a higher hydrogen dilution is needed to prepare micro-crystalline silicon, but in case of the n-μc-SiO:H an optimized hydrogen dilution was found suitable for higher X c . Observed X c of these films mostly decreased with increased plasma power (for pressure<2.0 Torr), increased gas pressure, flow rate of oxygen source gas and flow rates of PH3 >0.08 sccm. In order to determine deposition conditions for optimized opto-electronic and structural characteristics of the n-μc-SiO:H film, the gas flow rates, plasma power, deposition pressure and substrate temperature were varied. In these films, the X c, dark conductivity (σd ) and activation energy ( E a ) remained within the range of 0–50%, 3.5×10 −10  S/cm to 9.1 S/cm and 0.71 eV to 0.02 eV, respectively. Low power (30 W) and optimized flow rates of H2 (500 sccm), CO2 (5 sccm), PH3 (0.08 sccm) showed the best properties of the n-μc-SiO:H layers and an improved performance of a solar cell. The photovoltaic parameters of one of the cells were as follows, open circuit voltage ( V oc ), short circuit current density ( J sc ), fill-factor ( FF ), and photovoltaic conversion efficiency (η) were 950 mV, 15 mA/cm 2, 64.5% and 9.2% respectively.